Regulation of Villin by Wnt5a/Ror2 Signaling in Human Intestinal Cells - Cheung, Rebecca; Kelly, Jacqueline; Macleod, R. John (Frontiers in Physiology, 2011)
Regulation of expression of the intestinal epithelial actin-binding protein, villin, is poorly understood. The aim of this study was to determine whether Wnt5a stimulates Ror2 in intestinal epithelia caused transient increases in phospho-ERK1/2 (pERK1/2) and subsequently increased expression of villin transcript and protein. To demonstrate Wnt5a–Ror2 regulation of villin expression, we overexpressed wild-type, truncated, or mutant Ror2 constructs in HT29 adenocarcinoma cells and non-transformed fetally derived human intestinal epithelial cells, added conditioned media containing Wnt5a and measured changes in ERK1/2 phosphorylation, villin amplicons, and protein expression by RT-PCR and Western blot techniques. Wnt5a addition caused a transient increase in pERK1/2, which was maximal at 10 min but extinguished by 30 min. Transient transfection with a siRNA duplex against Ror2 diminished Ror2 amplicons and protein and reduced the extent of pERK1/2 activation. Structure–function analysis revealed that the deletion of the cysteine-rich, kringle, or tyrosine kinase domain or substitution mutations of tyrosine residues in the intracellular Ser/Thr-1 region of Ror2 prevented the Wnt5a stimulation of pERK1/2. Deletion of the intracellular proline and serine/threonine-rich regions of Ror2 had no effect on Wnt5a stimulation of pERK1/2. The increase in villin expression was blocked by pharmacological inhibition of MEK-1 and casein kinase 1, but not by PKC and p38 inhibitors. Neither Wnt3a nor epidermal growth factor addition caused increases in villin protein. Our findings suggest that Wnt5a/Ror2 signaling can regulate villin expression in the intestine.